(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Data compression is a method of bit reduction technique that uses a smaller amount of bits to represent information. A universal compression scheme is needed rather than unique methods for unique data formats. Data compression offers an approach for reducing communication costs, at the same time it is vulnerable to attack during the transmission. If it is compromised then it is not possible to get actual data during the decompression. Therefore security is needed to preserve the compressed data. Compression always relies on high redundant data in order to gain size reduction. The exponential growth equation for image encryption has provided less security against differential and statistical attacks. So, logarithmic function and the Henon-chaotic function for image encryption of heterogeneous data is proposed. It has two stages. At first, to minimize the intensity of the pixel esteems the natural logarithmic function of the image can be utilized and Image fusion is used to encrypt images using the key.